Merekabentuk dan membangunkan perisian alat ukur pengujian psikologi berasaskan teknologi perkhidmatan web: kajian fasa pengujian dan fasa implementasi pembangunan e-kaunseling. (peringkat ii) - Syed Yahya, Syed Mohd. Asri; Md. Ninggal, Mohd. Tajudin (Faculty of Education, 2004)
E-Kaunseling development is part of the research efforts undertaken to develop psychological testing based on the internet application software. The development of research is focus on 5 Actors that are General User, Application User, Recruitment Panel, Psychological Expert and Web Engineer. These Actors will be the catalyst to a dynamic counseling environment. e-Kaunseling offers reliable services as Personality Testing, Career Interest Testing, Account of User Profile Record Testing Analysis, Electronic Counseling Forum, Database and Knowledge- Base Control. Hopefully this application can be used by college and university students seeking information related to personality and career interest. It also can be used as an expert system (ES) that can generate a decision support system (DSS) analysis report for organization that involve in the management and structuring of human capital resources. This research also includes e-Kaunseling prototype development that uses purely Java 2 Enterprise Edition (J2EE) as the core of development technology. It uses the Web Engineering Management Strategy and Unified Modeling Language (UML) approaches. The e-Kaunseling research results are suitable as references to many web services based technology application software developers.